NLRC5 Serves as a Pro-viral Factor During Influenza Virus Infection in Chicken Macrophages - Chothe, Shubhada K.; Nissly, Ruth H.; Lim, Levina; Bhushan, Gitanjali; Bird, Ian; Radzio-Basu, Jessica; Jayarao, Bhushan M.; Kuchipudi, Suresh V. (Frontiers in Cellular and Infection Microbiology, 2020)
Avian influenza viruses (AIVs) cause major economic losses to the global poultry industry. Many host factors have been identified that act as regulators of the inflammatory response and virus replication in influenza A virus (IAV) infected cells including nucleotide-binding oligomerization domain (NOD) like receptor (NLR) family proteins. Evidence is emerging that NLRC5, the largest NLR member, is a regulator of host immune responses against invading pathogens including viruses; however, its role in the avian immune system and AIV pathogenesis has not been fully explored. In this study, we found that NLRC5 is activated by a range of low and highly pathogenic AIVs in primary chicken lung cells and a chicken macrophage cell line. Further, siRNA mediated NLRC5 knockdown in chicken macrophages resulted in a significant reduction in AIV replication which was associated with the upregulation of genes associated with activated NFκB signaling pathway. The knockdown of NLRC5 enhanced the expression of genes known to be associated with viral defense and decreased innate cytokine gene expression following AIV infection. Overall, our investigation strongly suggests that NLRC5 is a pro-viral factor during IAV infection in chicken and may contribute to pathogenesis through innate cytokine regulation. Further studies are warranted to investigate the IAV protein(s) that may regulate activation of NLRC5.